DIPLOMATIC PRESENCE OF UKRAINE IN THE WORLD IN TODAY'S REALITIES IN THE CONTEXT OF DIGITALIZATION - Oleksander M. Bykov; Yuliia S. Palieieva (Alfred Nobel University Journal of Law)
The article is devoted to modern changes in Ukraine. They are connected with the digitization of the lives of ordinary citizens, as well as with changes in the diplomatic sphere. Today, using the usual tools is no longer effective. Rapid changes require the search for new, extraordinary and bold approaches. It was determined that digitization is a transition to modern, transparent and automated rules. Ukrainians will be able to personally monitor the transparency of the system and monitor the implementation of projects in real time. Even a year ago, it was possible to claim that the coronovirus infection COVID - 19 changed the usual way of life. But the war fundamentally affected the lives of Ukrainians, as well as their digital behavior. Today, even in the conditions of war, Ukraine is becoming a leader in the implementation of the most modern and boldest innovations. Our state was the first to equate a digital passport with an analog one. Also, Ukraine can become the first state in the world to initiate the digital establishment of diplomatic relations. This is undoubtedly a confirmation of Ukraine's leadership in the field of modern technologies. Despite the ancient roots of diplomacy, it cannot be unchanging. We are talking about the creation of new mobile and efficient embassies. It was determined that digitalization accelerates the speed of development of the state. The article states that digital diplomacy or e-diplomacy is defined as the use of the Internet and new information and communication technologies to achieve diplomatic goals. Another point of view boils down to the fact that digital diplomacy solves foreign policy problems with the help of the Internet.